Insoluble granite-grit allows broiler chicks to have better growth performance and gut health - Güray Erener; Nuh Ocak; Ali Vaiz Garipoğlu; Ahmet Şahin (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this study was to investigate the effects of insoluble granite-grit on growth performance and gut health status of broiler chicks. One hundred and sixty 14-day-old broiler chicks were allocated to experimental groups control and grit feeding. Each group included 80 birds divided by four replicates, each consisting of 20 birds, 10 males and 10 females. Feed intake, body weight gain, feed conversion ratio, carcass weight, dressing percentage, gut length, abdominal fat pad, and liver, heart, and gizzard weights were determined. Starter diet included 230 g crude protein (CP) kg−1 and 3.15 Mcal metabolizable energy (ME) kg−1 during the days 14 to 21; grower diet included 212 g CP kg−1 and 3.20 Mcal ME kg−1; and finisher diet included 190 g CP kg−1 and 3.20 Mcal ME kg-1. Control birds were fed broiler diets, while grit-fed birds were allowed to consume broiler diets, including 3% insoluble granite-grit. Grit feeding improved the final body weight (2268 vs. 2336 g) with better feed efficiency (2.03 vs. 1.95) and less feed intake (3780 vs. 3764 g). Grit feeding increased gizzard weight (31.63 vs. 48.00 g) without affecting carcass weight (1643 vs. 1708 g), dressing percentage (73.50 vs. 73.60%), liver weight (42.69 vs. 40.69 g), heart weight (12.00 vs. 11.63 g), abdominal fat pad (34.50 vs. 35.38 g), and gut length (229.3 vs. 220.7 cm) of broilers. Grit feeding affects daily gain, feed intake, and feed conversion ratio positively by increasing gizzard development and health.